Analisis faktor risiko kegagalan persalinan pervaginam pada ibu-ibu hamil dengan riwayat seksio Caesar kehamilan sebelumnya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Heru Pradjatmo - Risk factors of the faiture of vaginal delivery after previous Cesarean section history. Objective: To know factors influencing the success rate of vaginal delivery after previous Cesarean section history. Methods: Historical cohort Setting: Sardjito General Hospital Yogyakarta Participants: Women who delivered her child in Sardjito General Hospital between the year 1997 to 2001, and had previous Cesarean section history. Their delivery would be vaginally or recesarean section. The factors which were predicted affect the success of the vaginal delivery will be analyzed. The significance level of Odd Ratio was determined by logistic regression analysis. Results: There were 275 pregnant women with previous Cesarean section history reviewed, 110 (40%) patients successfully delivered the fetus vaginally and 165 (60%) patients unsuccessfully delivered the fetus vaginally and were undergone Cesarean section. Several factors that might influence the success of vaginal delivery were analyzed: place (OR =0.97